Early complete remission of osteoid osteoma with conservative medical management - Masahiro Yokouchi; Satoshi Nagano; Hirofumi Shimada; Shunsuke Nakamura; Takao Setoguchi; Ichiro Kawamura; Yasuhiro Ishidou; Setsuro Komiya (MDPI AG, 2014)
Osteoid osteoma is a benign bone tumor and causes persistent pain that is usually treated by surgery or ablation therapy. Conservative management with non-steroidal anti-inflammatory drugs (NSAIDs) is also used to avoid the morbidity associated with surgery or ablation therapy; however, it usually takes several years for the condition to resolve using conservative treatment. Our patient, a 10-year-old boy, presented with a 3-month history of a painful lesion in his leg. Plain radiography, bone scanning, computed tomography and magnetic resonance images showed the presence of a lesion with radiological features consistent with an osteoid osteoma of the cortex in the tibial diaphysis. The patient was treated with a usual dose of ibuprofen for 3 weeks. Within 3 weeks, his symptoms were almost completely resolved; he no longer needed NSAIDs and returned to normal life. Repeat imaging studies showed complete disappearance of the nidus within 2.5 years after the resolution of symptoms.